Discrete choice experiments: preference for the consumption of mezcal from Puebla - Marcos-Toxqui, Jessica Guadalupe; Espejel-García, Anastacio; Barrera-Rodiguez, Ariadna Isabel; Flores-Girón, Emmanuel (Revista Mexicana de Ciencias Agrícolas, 2026)
Mezcal is a regional distillate that has gained recognition in the alcoholic beverage market. Its acceptance is linked to its authenticity, process and use of natural resources, which give it typical sensory attributes. In this context, consumers play a central role in valuing these attributes. Discrete choice experiments are a helpful tool for identifying consumer preferences and their willingness to purchase various products. The purpose of this study was to identify the attributes that influence consumer preference and willingness to pay for a mezcal produced in the state of Puebla, as well as to determine consumer characteristics, using an experimental design based on discrete choice. Two hundred eighty-two online surveys were applied during 2024, which included sociodemographic data of the participants and 16 cards organized in eight pairs, generated using a fractional factorial design. Participants chose between two options or neither. The data were analyzed using a multinomial logit model. The results indicate that the most valued attributes are place of origin, variety and type of agave, type of production, designation of origin, and price. In addition, the marginal willingness to pay for each significant attribute with a positive sign was estimated. Consumers value attributes in mezcal related to the geographical origin, traditional process and authenticity of mezcal; however, they are not willing to pay for mezcal produced in the state of Puebla.